PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTU MEDIA POP-UP BOOK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK KELAS IV SDN 3 KRIAN - Agustin, Nurul (Jurnal Muassis Pendidikan Dasar, 2023)
The quality of learning is determined by the way the teacher provides services in learning and provides facilities to students in all student activities in learning activities, so that it influences student learning outcomes. However, the learning outcomes of fourth grade students at SDN 3 Krian-Sidoarjo on the great ideals sub-theme are many students who have not finished studying. From the results of observations with these problems, this study aims to increase student activity and learning outcomes. This type of research uses classroom action research (CAR) using four stages in each cycle including planning, action, observation and reflection. As for several techniques in data collection, namely observation data of student activities and test data. This study uses observational data analysis techniques and data on student test results. The results of research on student activity in cycle I reached 66%, increasing in cycle II to 80%. Student completeness in cycle I reached 60% and increased in cycle II to 90%. It can be concluded that the application of the cooperative learning model of the Teams Games Tournament (TGT) type assisted by pop-up book media can increase the activity of class IV students at SDN 3 Krian.